(untitled) (Journal of Biomedical Investigation, 2023)
Background: Exercise has been proven to be an effective means of glycemic control. However, the knowledge and the practice of exercises among patients with Type II diabetes mellitus is uncertain. Aim of study: The aim of this study was to investigate the knowledge and practice of exercises for glycemic control among patients with Type II diabetes mellitus in Lagos, Nigeria. Materials and Methods: This cross-sectional analytical survey was carried out involving 140 (90 females and 50 males) patients with Type II diabetes mellitus. They were recruited from selected hospitals in Lagos State, Nigeria. A questionnaire was used to obtain information on the knowledge and pattern of practice of exercises among these patients. Spearman’s rank order correlation was used to determine the relationship between selected socio-demographic characteristics and knowledge and practice of exercises. The level of significance was set at p ≤ 0.05. Results: The knowledge of exercise among respondents was good (mean score of 55.45 ± 8.79 out of a maximum score of 72). A good number (72.1%) of the respondents indicated regular practice of exercises. There was a significant correlation between age, level of educational attainment and knowledge and practice of exercise (p< 0.05). There was also a significant correlations between monthly income and practice of exercise (p= 0.001) but there was none between monthly income and knowledge of exercise by the patients. Conclusion: There was a high level of knowledge and practice of exercise among patients with Type II diabetes mellitus and these were influenced by their age and level of educational attainment.